Estudio sobre los efectos locales del cambio climático y fenómenos meteorológicos en la provincia de Cotopaxi - Caicedo Sandoval, Cristina Elisabeth (2017)
The climatic instability is a problem that is currently causing variation in the climatic periods, mainly changing temperatures and rainfall, which has triggered various meteorological phenomena as scarce rainfall, extreme rainfall, flooding or droughts. The annual meteorological information was organized and systematized from the stations of the province of Cotopaxi: Rumipamba-Salcedo, Cotopaxi - Clirsen, Pilaló, El Corazón and San Juan - La Maná of the INAMHI through a statistical analysis of the annual meteorological records and identify areas that have had the impact of climate change through the occurrence of extreme weather events. It was collected from the years 1986 until 2015 stations located in Salcedo, Latacunga, Pujilí, Pangua and La Mana cantons respectively, the information was organized and systematized through statistical means to generate a meteorological database that helped with the development of Gaussen diagram for variation or existing climate displacement between the dry season and wet season of the study area; Finally the dry season expands on the stations in the Andean Region and occurs in the months of June-August. What is considered involvement area because of drought, while in the Suptropic it is reduced, accordingly the wet season extends in this region, between September and mid May.